Fosfomycin-Overcoming Problematic In Vitro Susceptibility Testing and Tricky Result Interpretation: Comparison of Three Fosfomycin Susceptibility Testing Methods - Jan Závora; Gabriela Kroneislová; Marie Kroneisl; Václava Adámková (MDPI AG, 2024)
Background: Fosfomycin (FOS) is an older antimicrobial agent newly rediscovered as a possible treatment for infections with limited therapeutic options (e.g., Gram-negative bacteria with difficult-to-treat resistance, DTR), especially in intravenous form. However, for correct usage of FOS, it is necessary to have a reliable susceptibility testing method suitable for routine practice and robust interpretation criteria. Results: The results were interpreted according to 2023 interpretation criteria provided by the European Committee on Antimicrobial Susceptibility Testing (EUCAST). DTR Gram-negatives were more likely to be resistant to FOS (45% in Enterobacterales and 20% in P. aeruginosa) than non-DTR (10% and 6.7%, resp.). All isolates of S. aureus were susceptible to FOS. In Gram-negatives, all agreement values were unacceptable. Etest® performed better in the DTR cohort (categorical agreement, CA, 80%) than in the non-DTR cohort (CA 45.7%). There were no very major errors (VREs) observed in P. aeruginosa. S. aureus had surprisingly low essential agreement (EA) rates (53% for MRSA and 47% for MSSA) for Etest®, but categorical agreement was 100%. Methods: A total of 130 bacterial isolates were tested and compared using the disc diffusion method (DD) and gradient strip method (Etest®) with the reference method (agar dilution, AD). The spectrum of isolates tested was as follows: 40 Enterobacterales (20 DTR vs. 20 non-DTR), 30 Pseudomonas aeruginosa (15 DTR vs. 15 non-DTR), and 60 Staphylococcus aureus (30 methicillin-susceptible, MSSA, vs. 30 methicillin-resistant, MRSA). Conclusions: Neither one of the tested methods was identified as a suitable alternative to AD. It would be beneficial to define more interpretation criteria, at least in some instances.